Method of construction of resource mapping in project management - Чімшір, Валентин Іванович (Eastern-European Journal of Enterprise Technologies, 2012)
The method of the establishment and maintenance of the resource map is proposed. The classification of the project operations, depending on the increasing of the resource investments is investigated. For each type of classification a possible measures of manipulations are identified